International Implications of European Economic and Monetary Union - Funke, Norbert (OECD Economics Department Working Papers, 1997)
For a long time European Economic and Monetary Union was mainly considered an internal European issue and external consequences were largely ignored. In contrast to most previous analyses, this paper looks at a number of international implications of monetary union. It is argued that several factors could contribute to the euro becoming an international currency in the future and a competitor to the US dollar in this respect. The degree of uncertainty attached to this outcome, however, remains considerable and in any event the emergence of the euro as a major international currency is likely to take some time. Given the expected size of the euro-zone and the likelihood of the euro becoming an international currency, fiscal and monetary policies in the area are likely to have a significant impact on the macroeconomic environment in the rest of the world. An important issue is how will monetary union affect major bilateral exchange rate developments and their volatility. A number of ...